Gestión de Alojamiento - HO178 - 202302 - Chue Rosell, Gonzalo Rafael (2023)
It is a Hospitality and Administration program-specific course of a theoretical and practical nature, aimed at six- term students. The course brings together and focuses on the key concept of Revenue Management, and then relates it to other managerial tools. Particular emphasis is on performance at the level of finance, the guest- service encounter, Strategic and Operation Planning , and understanding consumer behavior. The aim of this course is to further develop the students understanding of managerial and operational practices within a Rooms Division department, and seeks to develop the specific competencies ACPHA: Operational Management (Level 2) and Leadership (Level 2).